A solid-nitrogen cooled high-temperature superconducting magnet for use in magnetohydrodynamic marine propulsion - Hales, P; Hirst, P; Milward, S; Harrison, S; Jones, H (2006)
A small high-temperature superconducting (HTS) magnet has been produced as part of a magnetohydrodynamic (MHD) propulsion unit to power a model boat. The magnet is wound from 6 pancake coils of Bi-Sr-Ca-Cu-O HTS tape (BSCCO-2223), and is conduction cooled using an onboard "thermal battery", containing 3 liters of solid nitrogen. The magnet is racetrack shaped, and aluminum electrodes are placed along the straights of the magnet to pass an electric current through the saltwater, perpendicular to the magnetic field. Power for the magnet and the electrodes is provided by onboard sealed lead acid batteries, resulting in a fully 'stand-alone' magnet system, capable of up to 1.25 hours of continuous operation on one battery pack. This system was integrated into a model boat hull (approx. 1.2 m long x 0.6 m wide), which was successfully launched on 29th March 2004 at the Culham Science Centre in Abingdon, England. A top speed of similar to 30 mm/see was reached during the first,trial.